Stakeholder Analysis Program Jaminan Pangan Masyarakat (JAPANGMAS) oleh PT Pertamina (Persero) Fuel Terminal Rewulu - Afry Rakhmadany; Muhammad Tahsinurridlo; Laili Fauziyah; Nova Arinda Rahmawati; Siti Aidah (UIN Siber Syekh Nurjati Cirebon, 2020)
According to regional division database in 2017, the percentage of poverty rates in Indonesia is 10.27% in urban areas and 16.31% in rural areas. Through Corporate Social Responsibility (CSR), PT. Pertamina (the Company) Fuel Terminal Rewulu contributes to accomplish sustainable economic development in Dusun Samben in order to improve the quality of life and the environment that benefits the company itself, the local community, and the wider community. In the process of CSR implementation, it is necessary to do social mapping in order to analyze potential stakeholders who can assist the programs. The objectives of this study is to conduct potential stakeholder to determine who will be involved in the program. The analytical method used is descriptive qualitative with data collection techniques in the form of interviews and documentation. This study recommends some individuals and agencies that will potentially support the CSR program. The results showed that in the process of program planning requires stakeholder analysis in determining the actors involved in the program. The aim is to identify the interests, preferences, and the impact of the stakeholders on the program. With the result that in order to determine the right stakeholder to be involved, will build a massive foundation for the upcoming implementation of the program.